High-Quality Ruddlesden-Popper Perovskite Films Based on In Situ Formed Organic Spacer Cations - Qing, Jian (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.